2014
DOI: 10.1371/journal.pone.0100285
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of TSG-6 Engineered iPSC-Derived MSCs on Experimental Periodontitis in Rats: A Pilot Study

Abstract: BackgroundWe derived mesenchymal stem cells (MSCs) from rat induced pluripotent stem cells (iPSCs) and transduced them with tumor necrosis factor alpha-stimulated gene-6 (TSG-6), to test whether TSG-6 overexpression would boost the therapeutic effects of iPSC-derived MSCs in experimental periodontitis.MethodsA total of 30 female Sprague-Dawley (SD) rats were randomly divided into four groups: healthy control group (Group-N, n = 5), untreated periodontitis group (Group-P, n = 5), iPS-MSCs-treated and iPSC-MSCs/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 37 publications
1
60
0
Order By: Relevance
“…iPS cells have also shown, in vitro, expression of periodontal tissue markers associated with bone, periodontal ligament and cementum under the influence of enamel matrix derivative (EMD) and growth/differentiation factor-5 (GDF-5) (42). Treatment of periodontitis with iPSC-MSC transfected with tumor necrosis factor gene 6 (TSG-6) have shown significant reduction of periodontal inflammation, with reduced levels of inflammatory infiltrates, proinflammatory cytokines and also inhibited the level of alveolar bone loss (43). …”
Section: Applications Ips Cells In Dentistry (Fig 1)mentioning
confidence: 99%
“…iPS cells have also shown, in vitro, expression of periodontal tissue markers associated with bone, periodontal ligament and cementum under the influence of enamel matrix derivative (EMD) and growth/differentiation factor-5 (GDF-5) (42). Treatment of periodontitis with iPSC-MSC transfected with tumor necrosis factor gene 6 (TSG-6) have shown significant reduction of periodontal inflammation, with reduced levels of inflammatory infiltrates, proinflammatory cytokines and also inhibited the level of alveolar bone loss (43). …”
Section: Applications Ips Cells In Dentistry (Fig 1)mentioning
confidence: 99%
“…Much research has been focused on investigating the potential of dental‐derived postnatal stem cells, periodontal ligament stem cells, dental pulp‐derived stem cells, stem cells from exfoliated deciduous teeth, dental follicle‐derived stem cells, dental apical papilla stem cells, and dental socket‐derived stem cells . In addition, studies have used induced pluripotent stem cells for periodontal regeneration . Literature suggests that the safest approach to cell therapy is autologous transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Yang et al . demonstrated that tumour necrosis factor alpha‐stimulated gene‐6 (TSG6) expressing iMSCs were capable of decreasing the inflammation in experimental periodontitis model and inhibiting alveolar bone resorption . Human MSCs have emerged as a promising therapeutic source for treating myocardial and limb ischaemia .…”
Section: Therapeutic Applications Of Imscsmentioning
confidence: 99%